Pharmacological management of allergic rhinitis in the elderly - Hansen, Juga; Klimek, Ludger; Hörmann, Karl (Drugs & aging, 2005)
An increasing number of elderly persons in our society experience allergic rhinoconjunctivitis. Different agents are used in the pharmacological treatment of allergic rhinitis, with histamine H1 receptor antagonists (antihistamines) being the most frequently prescribed class. However, drug therapy of aged persons differs to a degree from that in other age groups primarily because of quantitative pharmacotherapeutic problems. The main problems are co-morbidities and polymedication, which may lead to drug-drug interactions.
Elektronische Reproduktion der Druckausgabe
Gesehen am 18.03.2022